Regional Labor Mobility in Finland - Poghosyan, Tigran (Washington, D.C. : International Monetary Fund, 2018)
This paper analyzes regional labor mobility in Finland using two complementary empirical approaches: a VAR proposed by Blanchard and Katz (1992) and a gravity model. The results point to a relatively limited regional labor mobility in Finland compared to the U.S. and to EU peers. The limited regional labor mobility is associated with persistent unemployment differentials across regions. Some impediments to regional labor mobility are exogenous, such as large geographical distances across regions and relatively sparse population density, and explain about 23 percent of the variation in labor mobility. Others can be influenced by policy, such as further increase in wage flexibiltiy and reduction of housing costs. These impediments explain about 60 percent of the variation in labor mobility. Greater regional labor mobility could help reduce regional unemployment differentials, improve job matching efficiency, and remove pressures from regional fiscal redistribution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet